Lecturers' perceptions and experiences of Blackboard Collaborate as a distance learning and teaching tool via Open Universities Australia (OUA). (1st September 2020) - Chen, Julian Chengchiang; Dobinson, Toni; Kent, Sarah
ABSTRACT: Australian tertiary institutions offer online units to provide flexibility for students unable to attend classes on campus due to the constraints of distance and scheduling. While lecture materials and discussions can be accessed asynchronously, a synchronous element allows lecturers and students to interact in real time. Blackboard Collaborate, featuring videoconferencing, text, voice chat and interactive whiteboard, is a synchronous tool which can encourage a collaborative learning environment. This study explored seven lecturers' perceptions of, and experiences with Blackboard Collaborate in an Australian university setting. Quantitative data was collected and statistically analysed from responses to closed-ended items in an online survey. Qualitative data was gathered and thematically analysed from open-ended item responses and semi-structured interviews. Lecturers found that the use of Blackboard Collaborate motivated students, helped them to share knowledge, facilitated timely responses to student queries, enhanced interaction via multimodality and built virtual learning and teaching communities. Negative aspects were also noted, however, and included lecturers having to cope with technical glitches, a lack of face-to-face co-presence, delayed turn-taking in live sessions and difficulties with engagement due to suitable session scheduling.